PENGEMBANGAN SIKAP DAN PERILAKU SISWA YANG BERMORAL DALAM KEGIATAN PEMBELAJARAN DI SEKOLAH - Muhtadi, Ali (MAJALAH ILMIAH PEMBELAJARAN, 2011)
In addition to provision of art, science and technology, schools should also develop aspects of moral and religious values to establish the attitude and behavior of the nation's generation of noble character. Technically, the strategy of the student's attitude and the moral behavior development in learning activities at school can at least be pursued through an integration of four alternatives strategies. The first strategy is to integrate the curriculum content of the moral lesson that has been formulated into all relevant subjects, especially the subjects of religion, citizenship, and language (both Indonesian and regional languages). The second strategy is to integrate moral learning into everyday activities at school. The third strategy is to integrate moral learning into the programmed or planned activities. And the fourth strategy is to build communication and cooperation between schools and parents (of the students).